Identification and new record of tick species on livestock from district Dera Ismail Khan, Pakistan - Naimat Ullah; Muhammad Jamil; Muhammad Ramzan; Aisha Arshad; Muhammad Zeeshan ul Haq (Persian Journal of Acarology)
Abstract